A THEORETICAL FRAMEWORK FOR REFORMING THE MANAGEMENT OF FOREIGN RESERVES AND DETERMINING THEIR OPTIMAL SIZE FOR ACTIVE FISCAL POLICY - AN ANALYTICAL STUDY OF THE IRAQI ECONOMY - Taib Othman Abdurrazaq (Scholar Express Journals, 2025)
Determining the optimal size of foreign reserves has a major role in achieving optimal employment of the financial surpluses that accrue to different countries in their economies, and this issue occupies special importance in rentier economies such as the Iraqi economy because of the association of those reserves with the value of unstable exports. The research stems from the hypothesis that the Central Bank of Iraq was unable to set a clear policy for the employment of foreign reserves to determine the optimal size of those reserves and the best way to employ them and to prefer the employment of these reserves in more effective investment aspects. The research concluded with a set of results, the most prominent of which is that the continued presence of foreign reserves of Iraq in the US Federal Bank in the form of treasury bonds does not achieve optimal employment for them, and the research suggested the use of foreign reserves to establish a sovereign fund for investment to maximize returns and achieve liquidity by employing international expertise to manage it.
Keywords: foreign reserves; monetary policy; international financing